THE ROLE OF CONSUMER LENDING IN IMPROVING THE LIVING WELLBEING OF THE COUNTRY'S POPULATION - Yakhshimuratova Khasiyat Khudaibergenovn (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article deals with the role of consumer credit in improving the welfare of the population of the country, that is, improving the system of consumer credit eliminates the conflict between the needs of the population and the ability to meet them with current cash income activates demand and as a consequence, contributes to the welfare of the population.